1999
DOI: 10.1021/bp9900312
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Reaction Yield during Biotransformation of the Volatile and Chemically Unstable Compound β-Ionone by Aspergillus niger

Abstract: Biotransformation of beta-ionone by Aspergillus niger IFO 8541 was a complex system, due to the low precursor solubility in water (0.88 mol/m(3)) which gave a two-phase liquid system, its high volatility (vapor pressure 7.2 Pa), and its poor chemical stability. A dynamic model, considering transfers between organic, aqueous, and gas layers, was established. It also took into account the decrease in organic layer area exchange during a process, due to progressive precursor disappearance. Its solving needed sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…In other words, no phase-transfer limitation could be shown. This was quite surprising, because such limitation could occur even with reaction rates considerably lower (Grivel et al 1999;Grivel and Larroche 2001). This behavior probably resulted from the fact that the biphasic medium appeared to be an oil-in-water emulsion, thus giving a large exchange area (Gargouri 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, no phase-transfer limitation could be shown. This was quite surprising, because such limitation could occur even with reaction rates considerably lower (Grivel et al 1999;Grivel and Larroche 2001). This behavior probably resulted from the fact that the biphasic medium appeared to be an oil-in-water emulsion, thus giving a large exchange area (Gargouri 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Os compostos originados da biotransformação atingiram a concentração de 3,5 g/L após 400 h de reação. Compostos como 4-oxo-β-ionona, 2-hidróxi-β-ionona, 4-hidróxi-β-ionona, 2-oxo-β-ionona e 4-hidróxi-5,6-epóxi-β-ionona foram formados através da biotransformação 26 . Um tipo de monooxigenase do citocromo P450 de Bacillus megaterium (P450 BM-3) possui baixa atividade de hidroxilação de β-ionona.…”
Section: Biotransformaçãounclassified
“…139 The physicochemical parameters of that system were analyzed elsewhere. 140 In their paper, very interesting for its originality, Krings et al 141 reported the screening of submerged microbial cultures able to oxifunctionilize the sesquiterpene R-farnesene (59). One culture, identified as A. niger, exhibited the most versatile and attractive flavor profile.…”
Section: Fungi and Yeastsmentioning
confidence: 99%
“…The best yield, 3.5 g·L −1 , was obtained after 400 h of reaction . The physicochemical parameters of that system were analyzed elsewhere . In their paper, very interesting for its originality, Krings et al reported the screening of submerged microbial cultures able to oxifunctionilize the sesquiterpene α-farnesene ( 59 ).…”
Section: Biotransformation Processesmentioning
confidence: 99%